2017
DOI: 10.1038/npp.2017.285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amphetamine on Sensorimotor Gating and Neurocognition in Antipsychotic-Medicated Schizophrenia Patients

Abstract: Prepulse inhibition (PPI) of startle is being explored both as an indicator of target engagement for, and a biomarker predicting the sensitivity to, procognitive effects of drugs. We now report the effects of the pro-attentional drug, d-amphetamine, on PPI and neurocognition in antipsychotic-medicated schizophrenia patients and healthy subjects (HS) who were also tested in a targeted cognitive training (TCT) module. 44 HS and 38 schizophrenia patients completed a double-blind, placebo-controlled crossover stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
(84 reference statements)
1
13
1
Order By: Relevance
“…By contrast, PPI has been shown to be enhanced in healthy subjects by a number of drugs with different mechanisms, including atypical antipsychotics (Swerdlow et al, 2006; Vollenweider et al, 2006), amantadine (Swerdlow et al 2002), ketamine (Duncan et al, 2001), nicotine (Hong et al, 2008) and MDMA (Vollenweider et al, 1999). We have reported that AMPH acutely enhances PPI in some subgroups of healthy individuals (Talledo et al 2009) and in schizophrenia patients (Swerdlow et al 2018). Clearly, the ability of a drug to enhance PPI in healthy subjects, absent other information, is not a sufficient basis to propose its utility in a PACT strategy.…”
Section: 1 Discussionmentioning
confidence: 99%
“…By contrast, PPI has been shown to be enhanced in healthy subjects by a number of drugs with different mechanisms, including atypical antipsychotics (Swerdlow et al, 2006; Vollenweider et al, 2006), amantadine (Swerdlow et al 2002), ketamine (Duncan et al, 2001), nicotine (Hong et al, 2008) and MDMA (Vollenweider et al, 1999). We have reported that AMPH acutely enhances PPI in some subgroups of healthy individuals (Talledo et al 2009) and in schizophrenia patients (Swerdlow et al 2018). Clearly, the ability of a drug to enhance PPI in healthy subjects, absent other information, is not a sufficient basis to propose its utility in a PACT strategy.…”
Section: 1 Discussionmentioning
confidence: 99%
“…The antipsychotic-induced facilitation of dopamine autoinhibition, mediated by DAT blockade and D 2 autoreceptor stimulation, which may serve as an antipsychotic mechanism is depicted in Figure 3 . Although we have arrived at this hypothesis by analyzing multiple experimental observations, which sometimes lack corresponding human studies, our functional predictions on the association between extracellular dopamine and antipsychotic therapeutic responsiveness in humans and animals have been observed by a number of independent groups (35, 38, 4548, 49, 218). In the following section, we will provide naturalistic examples of the potential importance of functional DAT to understanding antipsychotic-resistant schizophrenia.…”
Section: Dopamine Autoinhibition As a Feature Of Antipsychotic Responmentioning
confidence: 99%
“…Electroencephalographic (EEG) biomarkers of early auditory information processing (EAIP) are promising tools in experimental medicine, which may help parse the heterogeneity of responses to TCT and other procognitive interventions 39,40 . We have demonstrated the utility of EAIP biomarkers, including ASSR, as sensitive measures of target engagement and therapeutic sensitivity in neural mechanisms relevant for learning, memory, and cognitive rehabilitation [40][41][42][43] . Findings from these experimental medicine studies suggest that assessments of baseline (e.g., event-related activity recorded prior to the initiation of TCT or other pro-cognitive interventions) and the capacity for change or "malleability" of the underlying neural circuitry in response to acute or limited "doses" of TCT may predict future TCT-related outcomes 44,45 .…”
Section: Introductionmentioning
confidence: 99%